Pengaruh Iklim Organisasi Terhadap Kinerja Karyawan Melalui Etos Kerja Sebagai Variabel Mediasi - Andi, Aysha Zalika Ardita Putri (Universitas Terbuka, 2024)
This research was conducted to analyze the factors that influence employee performance at PT Bumi Jasa Utama Jakarta during the Covid-19 pandemic. The theoretical basis used is the Human Relations theory put forward by Elton Mayo which emphasizes the importance of a comfortable work environment in improving employee performance through increasing work morale. This research is quantitative research by collecting data through g-forms and related literature,and using regression analysis techniques with the SPSS program. The research results show that organizational climate and work ethic have a simultaneous influence on employee performance during the Covid-19 pandemic. However, organizational climate does not have a significant partial influence on employee performance, while work ethic has a significant partial influence. The conclusion of this research is that during the Covid-19 pandemic, organizational climate did not have a significant influence on employee performance, but had a positive influence on work ethic. Meanwhile, work ethic has a significant positive influence on employee performance, and organizational climate has a significant positive influence on employee performance through work ethic as a mediating variable. The results of this research confirm the relevance of Human Relations theory in the context of the Covid-19 pandemic.